Analisis Hukum Ekonomi Syariah terhadap Praktik Sewa Menyewa Tanah dengan Sistem Pembayaran Hasil Panen (Studi Kasus di Gunung Papandayan Desa Cisero Kecamatan Cisurupan Kabupaten Garut) - Syaripudin, Enceng Iip; Rosita, Rosita (STAI Al Musaddadiyah Garut, 2022)
Abstract Rent or also called ijarah is a concept in Islamic economics as a solution in increasing economic development, especially to improve the local economy located on Mount Papandayan Cisero Village, but in fact the people of Cisero Village still do not understand the existence of Sharia Economic Law. So it is necessary to study Sharia Economic Law, especially the land lease agreement that occurs in Cisero village so that the agreement does not deviate from Islamic teachings. The formulation of the problems examined in this study are, 1) How is the rental mechanism that is happening in Cisero Village 2) how is the analysis of Sharia Economic Law on rental practices in the Crop Payment System in Mount Papandayan, Cisero Village, Cisurupan District, Garut Regency. The objectives of the study are: 1) to find out how the leasing mechanism is happening in Cisero Village, (2) To analyze the Sharia Economic Law on the practice of renting land with a crop payment system in Mount Papandayan, Cisero Village, Cisurupan District, Garut Regency. The research methods used are field research and library research. This research is qualitative research, which is descriptive normative research. The result of research in Cisero Village, Cisurupan District, is that the community around the village conducts transactions with a crop payment system. Then both parties risk the results of the plant that is the object of the lease, namely the crop, and the crop is very unlikely to be able to produce or harvest and it cannot be ensured that the agreement is fulfilled according to the agreement. There is a chance from both parties (maysir), and uncertainty (gharar) in the implementation of land leases in Mount Papandayan, Cisero Village, Cisurupan District, so it can be concluded from the results of this study that the land lease agreement that occurred in Cisero village after being analyzed according to Sharia Economic Law that the practice is not allowed because of the non-fulfillment of one of the lease conditions and the practice is contrary to principles of Sharia Economic Law.